2015
DOI: 10.12659/aot.893648
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Donor Factors to Post-Reperfusion Severe Hyperglycemia in Patients Undergoing Living Donor Liver Transplantation

Abstract: PRSH development was heavily influenced by donor-related factors. Graft size, extent of fatty change, and post-reperfusion syndrome were identified as independent donor-associated predictors of PRSH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Severe macrovesicular steatosis (>60% steatosis) has a strong correlation with primary non-function (PNF), while moderate macrovesicular steatosis (30~60% steatosis) leads to damage in liver function and regeneration [ 23 ]. A recent study identified hepatic steatosis as an independent donor-associated risk factor of post-reperfusion severe hyperglycemia (PRSH) in patients undergoing LDLT [ 24 ]. Therefore, preoperative evaluation of hepatic steatosis is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Severe macrovesicular steatosis (>60% steatosis) has a strong correlation with primary non-function (PNF), while moderate macrovesicular steatosis (30~60% steatosis) leads to damage in liver function and regeneration [ 23 ]. A recent study identified hepatic steatosis as an independent donor-associated risk factor of post-reperfusion severe hyperglycemia (PRSH) in patients undergoing LDLT [ 24 ]. Therefore, preoperative evaluation of hepatic steatosis is essential.…”
Section: Discussionmentioning
confidence: 99%
“…The standardized surgical technique and anesthetic care, including glycemic control, for LDLT have been described in detail previously [15][16][17]. Briefly, intraoperative glycemic control was performed in accordance with the insulin infusion protocol of Yale University [18].…”
Section: Glycemic Control During Ldltmentioning
confidence: 99%